2022
DOI: 10.1111/ppl.13771
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and methylation analysis of susceptible and tolerant grapevine genotypes following Plasmopara viticola infection

Abstract: Downy mildew, caused by the biotrophic oomycete Plasmopara viticola, is one of the most economically significant grapevine diseases worldwide. Current strategies to cope with this threat rely on the massive use of chemical compounds during each cultivation season. The economic costs and negative environmental impact associated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…In contrast, the compatible interaction was characterized by hypermethylation at the same time point [ 25 ]. Similarly, Azevedo et al [ 89 ] reported that a grapevine genotype tolerant to P. viticola exhibited lower methylation levels compared to a susceptible genotype and displayed an early enhanced expression of defense- and epigenetics-related genes upon infection. Another study, though, in Arabidopsis revealed that transgenerational systemic acquired resistance against H. arabidopsidis failed in mutants impaired in RNA-directed DNA methylation (RdDM) [ 90 ].…”
Section: Epigenetics and Defense Responses To Pathogensmentioning
confidence: 99%
“…In contrast, the compatible interaction was characterized by hypermethylation at the same time point [ 25 ]. Similarly, Azevedo et al [ 89 ] reported that a grapevine genotype tolerant to P. viticola exhibited lower methylation levels compared to a susceptible genotype and displayed an early enhanced expression of defense- and epigenetics-related genes upon infection. Another study, though, in Arabidopsis revealed that transgenerational systemic acquired resistance against H. arabidopsidis failed in mutants impaired in RNA-directed DNA methylation (RdDM) [ 90 ].…”
Section: Epigenetics and Defense Responses To Pathogensmentioning
confidence: 99%
“…Overall, future directions have been proposed and discussed that indicate groundbreaking approaches that could promote the following: tolerance of powdery mildew caused by the biotrophic oomycete Plasmopara viticola in grapevine (Azevedo et al, 2022); acclimation to stressful conditions during sowing and seedling establishment in wheat (Hidvégi et al, 2022); phenological adjustment of budbreak and flowering in apple (Lempe et al, 2022); and adaptation to both chronic heavy metal contaminations (Jopčík et al, 2022; Karalija et al, 2022) and continuous climate change (Alves et al, 2022).…”
mentioning
confidence: 99%
“…The contributions of three epigenetic mechanisms (DNA methylation, histone post-translational modifications, and enzymatic regulation) are also described and discussed. The reported studies aimed to describe how plants acclimate to abiotic environmental constraints (Alves et al, 2022), including low temperature and drought in early stages of winter wheat seedling establishment (Hidvégi et al, 2022), frost risks in budbreak and flowering stages of apple crops (Lempe et al, 2022), chronic heavy metal contamination in hyperaccumulating plants (Karalija et al, 2022) or flax (Jopčík et al, 2022) in the radioactive Chernobyl area, and biotic stresses such as powdery mildew caused by Plasmopara viticola in grapevine (Azevedo et al, 2022). Most also discussed the contributions of epigenetic regulations in acclimation processes or their evolution under continuous climate change generally, and/or in specific taxa, such as members of the Fagaceae family (Alves et al, 2022).…”
mentioning
confidence: 99%
See 2 more Smart Citations